#TITLE_ALTERNATIVE# - RAFSANJANI OP (NIM 15102009), FARRID
The height determination process from building objects can be done by overlaying data from aerial photogrammetry with Digital Terrain Model (DTM) data. There are few method of interpolation used to determine the position of building coordinates in pixel coordinate system, which are Nearest Neighbor Interpolation method, Cubic Interpolation method, Bicubic Interpolation method. From analyzing the data processing process, it shown that for area with steep slope is better using the cubic interpolation method than nearest neighbor interpolation method because the result of data processing of cubic interpolation method is more precise than nearest neighbor interpolation method. This precision is needed for determine the building position accurately. But the calculation in the cubic interpolation method is more complicated. And for BiCubic Interpolation, the result of data processing is very extreme than both method above.